Destruction of Narcotic Drugs and Psychotropic Substances as a Stage of Circulation of Medicines - T. L. Malkova; E. S. Berezina (Разработка и регистрация лекарственных средств)
Introduction. Destruction is one of the stages of the circulation of medicines. Special importance is attached to this stage in relation to drugs related to narcotic drugs and psychotropic substances. The activities of pharmacy and medical organizations in relation to the turnover of these funds are strictly regulated.Aim. The purpose of the study was to study the procedure for the destruction of narcotic drugs and psychotropic substances included in Lists II and III of the List, as a stage of the circulation of medicines, to identify trends in the appointment of individual drugs for pain relief based on the generalization of archival data of the commission on destruction established on the basis of the Perm State Pharmaceutical Academy.Materials and methods. Archival materials of the destruction commission for 2012–2021 were used in the execution of the work. Each archive folder for a certain month of the year included the following documents: an order for the commission on destruction and appendices, a set of documents and acts of destruction for each institution that provided medicines. Statistical and empirical methods were used, such as observation, description, study, generalization and grouping, comparison, proof.Results and discussion. Data on prescribing drugs to cancer patients and data on drugs submitted for destruction correlate. Therefore, the range and quantity of medicines transferred for destruction by medical institutions allows us to see trends in their appointment and use in medical practice.Conclusion. Optimization of activities related to the turnover of controlled substances can be ensured by building a clear algorithm of actions in a medical organization for each type of work and services specified in the license, including the type of work – destruction. The procedure for the destruction of narcotic and psychotropic drugs, which is accompanied by verification of accompanying documents and objects at the meetings of the commission, allows monitoring the use and accounting of drugs in medical institutions.